Manajemen Pelayanan Anak Berkebutuhan Khusus Melalui Supervisi Diskusi Di Sekolah Dasar Alam Insan Mulia (SAIM) Surabaya - Muhammad Yusuf Aminuddin (TADARUS, 2016)
Education in Indonesia is granted to all citizens according to regulations, there is no discrimination in access to education. The same opportunities for education for all Indonesian citizens in line with the Dakar Declaration of 2000 on the World education forum produce a global agreement that education for all. Education that unites normal children with physically disabled children, children who have more ability or referred to children with special needs in one place is called inclusive education. One of the designated schools are elementary Saim since July 2012. Service management crews by the class teacher is still very poor due to a special teacher comes only once in a month and the new second grade teacher who has been educated to take the training to become a master Special Advisor (GPK) , How to improve service to the crew in Saims Elementary School is Principal proper supervision to the teacher. Based on the stages of research that uses qualitative approach to research design action for three cycles obtained positive results for the school.